CHRONIC GLOMERULONEPHRITIS IN CHILDREN AND OPTIMIZATION OF DISPENSARY FOLLOW-UP - Mukhammadieva M. I (Web of Journals Publishing, 2026)
Chronic glomerulonephritis (CGN) represents a significant cause of chronic kidney disease and end-stage renal failure in pediatric populations worldwide. This comprehensive review examines the epidemiology, pathogenesis, clinical manifestations, and current therapeutic approaches for chronic glomerulonephritis in children, with particular emphasis on optimizing long-term dispensary follow-up strategies. The analysis synthesizes evidence-based recommendations for monitoring protocols, risk stratification, prevention of disease progression, and coordination of multidisciplinary care. Special attention is devoted to the transition from pediatric to adult nephrology services and the role of patient education in improving adherence and outcomes.
Keywords: Chronic glomerulonephritis, children, pediatric nephrology, dispensary follow-up, chronic kidney disease, renal replacement therapy, disease monitoring.